EFFECTS OF SHADE TREE SPATIAL DISTRIBUTION AND SPECIES ON PHOTOSYNTHETIC RATE OF COFFEE TREES - Silva Neto, Francisco José da; Bonfanti, Leila; Gazaffi, Rodrigo; Fontanetti, Anastácia (Coffee Science - ISSN 1984-3909, 2019)
The use of shade trees in coffee fields have been motivated by climatic changes. However, microclimatic conditions in shaded coffee fields differ due to shade tree spatial distribution and species, altering physiological responses of coffee trees. This study aimed to evaluate the effects of shade tree spatial distribution and species on coffee trees photosynthetic rate in two growth seasons, of high (HSD) and low (LSD) sink demand. The experimental design consisted of randomized blocks with three replicates in split-split-plots. Plots were the shade tree species: Anadenanthera falcata, Cassia grandis and Peltophorum dubium. Split plot was formed by five distances between coffee trees and shade tree trunks: coffee trees on planting row of shade trees, distancing one (D1L) and five (D5L) meters from shade trees trunk; coffee trees on inter-rows of shade trees, parallel to D1L and D5L (D1E and D5E); coffee trees distancing 77 meters from shade tree trunks, in a full-sun field (PS). The split-split-plots correspond to coffee tree canopy exposure to the sun: branches facing North or South. Shade trees canopy density and occupation was evaluated with a convex densiometer. Photosynthetic rate (Pn)and photosynthetic active radiation (PAR) were measured with an Infrared Gas Analyzer (IRGA) on two time-frames, between 7.00 and 9.00 solar hours and between 11.00 and 13.00. Shade tree canopy density and occupation was not homogenous during the change of seasons and shift due to spatial distribution, which also changes PAR levels. Shade trees reduce PAR to more suitable values for coffee tree exploitation, especially on D1L and D5L. During HSD, shading did not affect Pn, which was greater in branches facing North. Yet, in LSD, between 11.00 and 13.00, coffee trees shaded with A. falcata showed greater Pn than at PS. Coffee trees shaded with C. grandis at D5L and D1E had greater values of Pn than PS.